Analysis of Rice Production Forecast in Maros District Using the Box-Jenkins Method with the ARIMA Model - Nurman, Sulaeman; Nusrang, Muhammad; Sudarmin (ARRUS Journal of Mathematics and Applied Science, 2022)
The Box-Jenkins method is a statistical method used for forecasting time series data. This method uses data in the past as the dependent variable. The data used in this study is data on the amount of rice production in Maros Regency which was taken from 2001 to 2018 which was taken from the Central Statistics Agency of Maros Regency and the Department of Food Security, Food Crops, and Horticulture of South Sulawesi Province. The results obtained show that the ARIMA(0,2,1) model is a suitable model to predict the amount of rice production in Maros Regency. Forecasting results show that the amount of rice production in Maros Regency has increased every year with an average increase of 3807.1 tons.